The Contribution of Mental Toughness to Competitive Anxiety in U-15 SSB Tunas Inti at Sungai Penuh City Football Athletes - Muhammad Algipari; Susanto, Nugroho (JOURNAL RESPECS (Research Physical Education and Sports), 2023)
When facing challenges, especially during competition, mental toughness is a positive trait that must be possessed, but competitive anxiety is a negative trait that must be possessed when facing challenges. The purpose of this study was to determine the attitude towards mental toughness and competitive anxiety and how mental toughness influences competitive anxiety in SSB Tunas Inti FC athletes in Sungai Penuh City. This type of research involves quantitative research in the field of statistics. The research design in question utilises an associative approach with quantitative precision. All 195 SSB Tunas Inti U-15 football players from Sungai Penuh City became the subject of this study. Purposive sampling is the method used in collecting data in this study to obtain a sample of 22 athletes who fall into certain categories. In this study, data was collected using an assessment tool that measures competitive anxiety and mental toughness on two different scales. This study uses product moment analysis techniques while testing the hypothesis using a test of determination, especially with the coefficient of determination. Each computation used for the calculations in this study uses SPSS 29.0 statistics. The findings of this study reveal that mental toughness is at the midpoint of the scale (21 out of 22 respondents) and competitive anxiety is at the low point (13 out of 22 respondents). In contrast, the correlation coefficient between mental toughness and competitive anxiety in soccer athletes is shown to be between 0.039 and 0.864 > 0.05. Therefore, it can be concluded that there is no connection between mental toughness and competitive anxiety. To determine the relative contribution between the mental toughness and competitive anxiety variables, a value of 0.039 is used, with this value located at a very low correlation coefficient interval.